Integrated analysis of inventory management and transportation systems for the single-period problem - Abdul Rahim, Mohd Kamarul Irwan; Radzuan, Kamaruddin; Yaakob, Mazri (American Scientific Publishers, 2016)
In a two-stage supply chain system, vendor managed inventory policies (VMI) is an integrating decisions between a supplier and his customers.The supplier assumes the responsibility of maintaining inventory at its customers and ensuring that they will not run out of stock at any moment.The objective of this paper is to optimize the inventory and the transportation costs of the customers for a two-stage supply chain. The problem is to determine the delivery quantities as well as the times and routes to the customers, while ensuring feasibility regardless of the realized demands.This paper considers the single-period stochastic inventory routing problem (SP-SIRP) system. The problem formulated as a linear mixed-integer stochastic program for the solutions of the SP-SIRP problem. An illustrative example for the SP-SIRP is presented to explain the proposed model. The finding shows that the vehicle capacity is optimized efficiently with the average capacity utilization for all tours is 100%.